Lubang Tambang Batu Bara Bayah: Jejak Romusha di Banten Selatan - Iwan Hermawan (Balai Arkeologi Maluku, 2017)
Romusha was a form of labor force mobilization during the Japanese occupation. They are employed to build military infrastructure and explore mining or digging foxholes. One of the center of romusha was Bayah in South Banten. Romusha were came from different parts of Java Island and employed in the Bayah Kozan coal mine. The coal mining system carried out in Bayah, is a closed mine. Mining is done by making a hole to reach ader (ore tree). The mining pits and coal mining activities were conducted with simple equipment under the pressure and torture of the Japanese soldiers who supervised romusha. This paper aims to uncover traces romusha in South Banten through the remains of Japan in the form of Coal Mine Hole. The writing method used is descriptive analysis. Data collection through the activities of literature studies, field surveys, and interviews. The suffering experienced by the romusha in Bayah reflected from the pits where coal mines are numerous in the region Gunungmadur Bayah.Romusha merupakan bentuk mobilisasi tenaga kerja pada masa Pendudukan Jepang. Mereka dipekerjakan untuk membangun sarana prasarana militer dan menggali bahan tambang atau lubang perlindungan. Salah satu daerah yang menjadi tempat pemusatan romusha adalah Bayah di Banten Selatan. Mereka berasal dari berbagai daerah di Pulau Jawa dan dipekerjakan di tambang batu bara Bayah Kozan. Sistem penambangan batu bara yang dilakukan di Bayah adalah tambang tertutup. Penambangan dilakukan dengan cara membuat lubang untuk mencapai ader, yaitu pohon bijih. Kegiatan penggalian lubang tambang dan penambangan batu bara dilakukan dengan peralatan sederhana di bawah tekanan dan siksaan tentara Jepang yang menjadi pengawas romusha. Tulisan ini bertujuan untuk mengungkap jejak romusha di Banten Selatan melalui tinggalan masa Jepang berupa lubang tambang batu bara. Metode penulisan yang digunakan adalah deskriptif analisis. Pengumpulan data melalui kegiatan studi pustaka, survei lapangan, dan wawancara. Penderitaan yang dialami oleh para romusha di Bayah tergambar dari keberadaan lubang-lubang tambang Batu bara yang banyak terdapat di kawasan Gunungmadur, Bayah.